Sarawak State Library Herbal Garden - Chan, Margaret (UiTM Sarawak, 2015)
The Faculty of Plantation and Agrotechnology was involved in the rehabilitation projects of the Sarawak State Library Herbal Garden in 2012. The garden was redesigned based on a theme that takes into consideration the herbal properties for culinary, medicinal, aromatic and pharmaceutical purposes. Some components were arranged in formal designs laid out as a series of beds creating some geometric forms like squares, circles or semicircles and other components in the form of an island. Hardscaping elements pulled all the components together with paths between the beds paved with circular cements blocks. After two years, the garden has matured under the tender care of the library staff and the occasional gotong royong activities by the students. 60 herbal plants are in the record list.